Physicochemical properties of chocolate spread with hazelnut cake: Comparative study and optimization - Acan, Betul Gizem; Toker, Omer Said; Palabiyik, Ibrahim; Pirouzian, Haniyeh Rasouli; Bursa, Kubra; Kilicli, Mahmut; Yaman, Mustafa; Er, Tugba; Konar, Nevzat (ELSEVIER, 2021)
The purpose of the current study was to evaluate the impact of hazelnut cake as a partial replacer for sugar, milk and whey powders on the chocolate spread. A D-optimal mixture design was used to determine the effect of different mixtures of sugar, total milk originated powders (MOP), as milk powder and whey powder, and hazelnut cake (HC) on the physicochemical properties, as well as in vitro digestion of total phenolic compound before and after digestion and its bioaccessibility. Results were described by appropriate mathematical models defined by using best-fitting analysis. According to the results, the fitted models illustrated a desirable coefficient of determination (>= 81%). The optimization of the variables indicated that using 43.562% sugar, 7.186% MOP and 7.252% HC produced the optimum chocolate spread with the highest desirability (1.00) without unwanted variations in the quality properties. The HC as an industrial by-product could be used in chocolate spread to increase bioactive compounds and also to decrease product costs by decreasing the sugar, milk and whey powder of the final product.
Keywords: Chocolate spread; Hazelnut cake; Optimization; Mixture design; CORYLUS-AVELLANA L.; PARTICLE-SIZE DISTRIBUTION; FLOW PROPERTIES; PROTEIN; MEAL; FAT; STABILITY; DIETS; FISH; Food Science & Technology